Увеличение рабочего магнитного потока под главным полюсом предельно нагруженного двигателя постоянного тока серии 4П280 путем уменьшения насыщения отдельных участков его магнитопровода - Козорезов, Александр Евгеньевич; Егоров, Борис Алексеевич (НТУ "ХПИ", 2009)
Статья посвящена проблеме повышения основного магнитного потока под главным полюсом на примере отрезке серии машин постоянного тока 4П280.

A problem of magnetic designing of DC motors is analyzed for so-called "limiting motors" in which it aggravate due to obtaining improved power indexes in its given limiting dimension. The problem is discussed in the paper
Increasing of working magnetic stream under the main pole of the 4П280 DC motor under maximum loading by reduction of satiation in separate areas of its magnetic system
Keywords: двигатели постоянного тока; магнитная система; DC motor; magnetic system; satiation; designing